Money demand in Indonesia and its forecasting to 2033 - Arif Imam Suroso; Saiful Bahri; Noer Azam Achsani; Suhendi; Linda Karlina Sari (Economies, 2025)
This study aims to identify the primary factors influencing the demand for money in Indonesia and to provide forecasts through 2033. The research employs two methodologies: time series econometrics and machine learning, utilizing data spanning from the first quarter of 2010 (2010Q1) to the fourth quarter of 2023 (2023Q4). The results of the study indicate that, in the long term, the demand for money in Indonesia is influenced by two main determinants: Gross Domestic Product (GDP) and Financial Institution Depth (FID). In the short term, the significant determinants include interest rates, inflation rates, GDP lag, FID lag, and electricity access. The forecast results suggest that the demand for money in Indonesia is projected to experience positive growth, reaching IDR 16,855,845 billion by 2033. This finding underscores the continued importance of physical currency in the Indonesian economy. Based on these results, this study serves as a guideline for policymakers in managing the demand for money by considering the variables that can either increase or decrease this demand. The positive forecast for the demand for money also highlights its significant role in supporting a stable Indonesian economy in the future.
Keywords: 330; business analytics; Indonesia; money demand; time series analysis